THE INFLUENCE OF BRAND IMAGE, SERVICE QUALITY AND PRICE PERCEPTION ON CONSUMER REPEAT PURCHASES AT ROXY SUPERMARKET JEMBER - Nabila, Revagita Maulida; Santoso, Budi; Izzudin, Ahmad (Universitas Muhammadiyah Tangerang, 2024)
Intense competition in the retail business is inseparable due to the proliferation of shopping centers both local, national, and international with various scales and segments. The objectives of this study are: 1) To find out whether brand image (brand image) affects the repurchase of Roxy Supermarket Jember consumers. 2) To find out whether service quality affects the repurchase of Roxy Supermarket Jember consumers. 3) To find out whether price perceptions affect the repurchase of Roxy Supermarket Jember consumers. This study uses associative research techniques with a quantitative approach. The population in this study were consumers who had bought products and visited the Roxy Square Jember supermarket and the sample of this study consisted of 85 people. The sampling technique here uses non-probability sampling with a purposive sampling approach. Data collection techniques using interviews and questionnaires. Hypothesis testing of this study using Partial Test (t-test). The results showed that: 1) Brand Image variable (X1) partially has a significant effect on Consumer Repurchase (Y). 2) Service Quality Variable (X2) partially affects Consumer Repurchase (Y). 3) Price Perception Variable (X3) partially affects Consumer Repurchase (Y).